2019
DOI: 10.3892/ol.2019.10908
|View full text |Cite
|
Sign up to set email alerts
|

Selective downregulation of distinct circRNAs in the tissues and plasma of patients with primary hepatic carcinoma

Abstract: Multiple studies have indicated that circular RNAs (circRNAs) are closely associated with malignant tumor development and metastasis. However, the significance of circRNAs in primary hepatic carcinoma (PHC), particularly in the plasma, remains largely undetermined. In the current study, circRNA expression profiles in three pairs of tumor and adjacent normal samples from patients with PHC, were examined using circRNA chip screening. A total of 80 circRNAs were upregulated, while 75 circRNAs were downregulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…1A, S1A and Table S2 -4). Due to 4 of these 8 circRNAs were deeply reported in HCC [15][16][17][18] , we then detected the expressions of the other 4 circRNAs by using 10 pairs of human tissues (HCC tissues vs. the correspondent non-tumor adjacent tissues). We found that circMRPS35 was the most significantly different expressed in HCC tissues (Fig.…”
Section: Results the Expression And Characteristics Of Circmrps35 In Hmentioning
confidence: 99%
“…1A, S1A and Table S2 -4). Due to 4 of these 8 circRNAs were deeply reported in HCC [15][16][17][18] , we then detected the expressions of the other 4 circRNAs by using 10 pairs of human tissues (HCC tissues vs. the correspondent non-tumor adjacent tissues). We found that circMRPS35 was the most significantly different expressed in HCC tissues (Fig.…”
Section: Results the Expression And Characteristics Of Circmrps35 In Hmentioning
confidence: 99%